Hysterectomy: the Indications and Results. A Study of (113) Patients in Duhok City - Razzak, Ala Hani (Sulaimani Journal for Pure and Applied Sciences, 2001)
This study included (113) patients who underwent hysterectomy from February 1998 to April 2000 in Azady General Hospital in Duhok City. The mean age for the included patients was (46.5) years. Abnormal uterine bleeding was the major indication for hysterectomy (68%) and the next common indication was lower abdominal pain, pelvic pain & backache (10.6%). Fifty two patients (46%) had no gross or microscopic pathology while endometrial hyperplasia was found in (18) patients (16%), adenomyosis in (11) patients (9,7%), Leiomyomas in (10) patients (8.8%), Endometrial polyps in (5) patients (4.4%) and only four patients had malignancies (3.5%); three of them had uterine malignancies and only one had ovarian cancer.
Keywords: Hysterectomy; Endometrail hyperplasia; Leiomyoma,endometrial Polyp